Natural Born Citizen as a Requirement of Indonesian President: Significances and Implications - Susi Dwi Harijanti; Firman Manan; Mei Susanto; Ilham Fajar Septian (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2020)
The Third Amendment to the 1945 Constitution stipulates that one of the requirements to become a presidential candidate is an Indonesian natural-born citizen who has never received another citizenship of his/her own volition. The requirement can create confusion and dissenting opinions to determine persons considered natural-born citizens and methods to prove it. This study explores the significances of determining a natural-born citizen as a requirement to become a presidential candidate and its implications. Through a socio-legal approach, this study concludes that the natural-born citizen requirement's significance is to eliminate racial discrimination from the previous requirement of a “native Indonesian” president and to ensure convincing allegiance from the president. There are some implications of the requirement. First, every Indonesian citizen born after the establishment of the Citizenship Law 2006, regardless of ethnic status, is called a natural-born citizen, including those from mixed marriages and having limited dual citizenship up to the age of 18 years. Meanwhile, for Indonesian citizens born before the Citizenship Law 2006, the natural-born citizen status is determined based on Law 3 of 1946 and Law 62 of 1958, including Indonesia’s agreement with the Netherlands and China. Second, a natural-born citizen status mutatis mutandis should require of other constitutional positions, either executive, legislative, or judiciary, and to a presidential candidate’s husband or wife.Natural Born Citizen sebagai Syarat Presiden Indonesia: Arti Penting dan ImplikasiAbstrakAmandemen Ketiga UUD 1945 menetapkan salah satu syarat calon presiden adalah kewarganegaraan sejak kelahiran (natural-born citizen) dan tidak pernah menerima kewarganegaraan lain karena kehendaknya sendiri. Syarat tersebut dapat menimbulkan kebingungan tentang siapa saja yang dapat dianggap sebagai warga negara sejak kelahiran dan bagaimana pembuktiannya. Tulisan ini bertujuan untuk menelusuri arti penting penetapan natural-born citizen sebagai syarat presiden dan implikasinya. Melalui pendekatan sosio-legal, artikel ini menyimpulkan arti penting syarat natural-born citizen adalah untuk menghilangkan diskriminasi rasial dari syarat presiden “orang Indonesia asli” dan untuk menjamin kesetiaan yang kuat dari presiden. Adapun implikasinya, pertama, setiap WNI yang lahir setelah berlakunya UU Kewarganegaraan tahun 2006, jika sejak kelahirannya telah berstatus WNI, tanpa melihat status etnis, disebut sebagai natural born citizen, termasuk di dalamnya berasal dari perkawinan campuran dan memiliki kewarganegaraan ganda terbatas sampai dengan usia 18 tahun. Sementara WNI yang lahir sebelum UU Kewarganegaraan tahun 2006, penentuan status WNI sejak kelahiran berdasarkan pengaturan UU 3 Tahun 1946 dan UU 62 Tahun 1958 termasuk perjanjian-perjanjian yang diadakan Indonesia dengan Belanda dan Tiongkok. Kedua, natural born citizen secara mutatis mutandis seharusnya diberlakukan bagi syarat jabatan ketatanegaraan lainnya baik eksekutif, legislatif, maupun yudikatif, serta terhadap suami atau istri calon Presiden karena alasan kesetiaan.Kata Kunci: kesetiaan, kewarganegaraan sejak kelahiran, syarat presiden.DOI: https://doi.org/10.22304/pjih.v7n3.a1